Effect of Four Weeks of Home-Based Balance Training on the Performance in Individuals with Functional Ankle Instability: A Remote Online Study - Mohammadreza Seyedi (MDPI AG, 2021)
The purpose of the current study is to evaluate the effect of 4 weeks of home-based balance training (HBBT) on the performance of individuals with functional ankle instability (FAI) in daily activities and sports. Thirty college students diagnosed with FAI and with a mean weight of 79.8 ± 3.4 kg, height of 182.5 ± 5.1 cm, age of 23.5 ± 1.2 years, and instability score of 20 ± 2.3 were selected to participate in this study and were randomly divided by computer-generated methods into two groups: the HBBT group and the control group (CG), each consisting of 15 subjects. The HBBT group performed the program at home for 4 weeks, while the CG was non-exercise. Before and after the 4 weeks of exercise program, a form containing the foot and ankle ability measure for daily activities and sports was completed by the individuals. For data analysis, intra- and inter-group comparisons were performed using paired and independent sample t-tests, respectively, at a significance level of p ≤ 0.05. The results showed that 4 weeks of progressive HBBT were sufficient to significantly improve the measurement of the ability of ankle and foot function in individuals with FAI, even with a total volume of only 60 min per week. Accordingly, it is suggested that individuals with FAI can benefit from short-term HBBT programs, which are simple yet powerful enough to promote improvements in daily activities.